Problems of shaping the media competence of future journalists on the basis of case studies - Abylgazova, Zh. A.; Akynbekova, A. B.; Golovchun, A. A. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
At a time when the digitalization of the world and the consequent transformation of the whole world is actively developing, the professional requirements of every field are beginning to be replenished. This is especially true of journalism, since through this profession we exchange information in the global sense of the word. Therefore, special attention is being paid to media literacy, as it is the core professional competence of the media today. Also, fact-checking is another important point. Living in the internet age offers great opportunities for personal development and trying out different roles. It has become very popular nowadays to develop one's social networking accounts. The public publish their thoughts, news, and part of it is not appealing reliable information. Consequently, the media competencies described in this article should be studied, and more importantly applied in their activities not only by the next generation of journalists, but also by people who view this profession as a hobby. After all, if we look at the meaning of "media competence", it is worth pointing out that it is primarily an understanding of the socio-cultural, economic and political context in the media. Consequently, the ability to be a bearer and transmitter of information requires the individual to meet media cultural standards and to interact effectively with media space, thereby creating new elements of the media culture of modern society.